Democratic Model of Public Policy Accountability. Case Study on Implementation of Street Vendors Empowerment Policy in Makassar City - KASMAD, RULINAWATY; ALWI, ALWI (Jurnal Studi Pemerintahan, 2015)
Policy accountability is a form of manifestation of public officials responsible to the people. One form of policy accountability that is discussed here is street vendors policy accountability, because they are a group of citizens who have the economic activities in public spaces. The existence of this policy how-ever, the number of street vendors from year to year increase in Makassar City. Therefore, this study seeks to uncover and explain the democratic policy ac-countability through the street vendors’ responses and expectations to the implementation of street ven-dors empowerment policy in Makassar City; and to uncover and explain the democratic policy account-ability through the stakeholders’ responses and ex-pectations to the implementation of street vendors empowerment policy in Makassar City. To achieve these objectives, the study uses democracy theory, in which this theory focuses on togetherness in dis-cussing solutions to the various problems of street vendors and in the policy implementation as well.This study used a qualitative design and case studies strat-egy. Data collection techniques used was observa-tion, interview, and documentation. Data were ana-lyzed with case description its settings. The results of this study pointed out that the interests and needs of the street vendors are not met through the empow-erment policies vendors. This is caused by the ab-sence of accountability forum as a place of togeth-erness all of street vendors empowerment stakehold-ers’. Street vendors empowerment policy in Makassar City are designed base on a top-down approach, so they are considered as objects, which must accept all government programs aimed at them